2019
DOI: 10.3390/foods8090386
|View full text |Cite
|
Sign up to set email alerts
|

Arthrospira Platensis (Spirulina) Supplementation on Laying Hens’ Performance: Eggs Physical, Chemical, and Sensorial Qualities

Abstract: The present study evaluated the effects of dietary supplementation of spirulina on laying hens’ performances: Eggs’ physical, chemical, and sensorial qualities. A total of 45 Lohman White hens, 44 weeks of age, were randomized into 3 groups of 15 birds. Hens were given 120 g/d of a basal diet containing 0% (control), 1.5%, and 2.5% of spirulina for 6 weeks. Albumen height and consequently Haugh unit were significantly affected by dietary supplementation of spirulina (p < 0.05) and by weeks on diet (p < 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…Recently, many studies have reported that dietary supplementation with L-carnitine ( Ghoreyshi et al., 2019a , Ghoreyshi et al., 2019b ; Ghoreyshi et al., 2019a , Ghoreyshi et al., 2019b ), quercetin ( Goliomytis et al., 2014 ), and saponins ( Bera et al., 2019 ) in broiler chickens improves meat quality. In addition, dietary supplementation with spirulina ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ), linseeds ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ), and fenugreek seeds ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ) has successfully improved the egg quality of laying hens. Hen eggs are considered one of the most healthy foods in nature because they contain high-quality proteins and lipids, as well as trace elements and vitamins ( Fredriksson et al., 2006 ; Walker et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have reported that dietary supplementation with L-carnitine ( Ghoreyshi et al., 2019a , Ghoreyshi et al., 2019b ; Ghoreyshi et al., 2019a , Ghoreyshi et al., 2019b ), quercetin ( Goliomytis et al., 2014 ), and saponins ( Bera et al., 2019 ) in broiler chickens improves meat quality. In addition, dietary supplementation with spirulina ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ), linseeds ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ), and fenugreek seeds ( Omri et al., 2019a , Omri et al., 2019b , Omri et al., 2019c ) has successfully improved the egg quality of laying hens. Hen eggs are considered one of the most healthy foods in nature because they contain high-quality proteins and lipids, as well as trace elements and vitamins ( Fredriksson et al., 2006 ; Walker et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a deeper egg yolk colour in the organic (ADS18 or Se-Yeast) treated group. Contrary, Omri et al [32] reported an increase in egg yolk redness and decreased yellowness with colorimetric determination when evaluating the effects of Arthrospira platensis (spirulina) supplementation on laying hens. However, the latter author [39] reported an increase of yellowness and decreased redness of eggs stored at 4 0 C for 30 days corresponding to linseeds-fed hens.…”
Section: Discussionmentioning
confidence: 96%
“…Dietary supplementation of carotene plays a vital role in egg yolk colour intensi cation [30], pigment (carotene) synthesis in hen eggs is feasible with its supplementation via diet's ingredients [31]. Microorganisms like algae, fungi some bacteria, and plants were reported to synthesized carotene pigments [32]. In the present study, egg yolk colour assessment was estimated by RYCF and CIELAB photo-calorimetric determination system of L* (lightness), a* (red), b* (yellow), chroma (saturation or colour intensity), and hue (colour tone).…”
Section: Discussionmentioning
confidence: 99%
“…Uses and applications of bioactive components cover a wide range of sectors, especially nutraceuticals [5][6][7]. In vitro [8] and in vivo [9] studies assessing the beneficial effects of nutraceutical models were presented, in particular studies on the nutritional supplements in animals [10][11][12]. At the same time, particular researches on botanicals have been described by [13][14][15] concentrating on the importance of those sources of vegetable origin (see Figure 1).…”
Section: Nutraceuticalsmentioning
confidence: 99%